Pengaruh Good Corporate Governance dan Leverage Terhadap Kinerja Keuangan Pada PT. Kimia Farma Tbk. Pada Tahun 2013-2018 (Ekonomika, 2020)
The Influence of Good Corporate Governance and Leverage on Financial Performance at PT. Kimia Farma Tbk. 2013-2018. This study aims to determine the influence of Good Corporate Governance and Leverage on Financial Performance at PT. Kimia Farma Tbk. Research period 2013-2018. The statistical analysis used in this study is multiple linear regression analysis used to test the influence of Good Corporate Governance and Leverage on a company's financial performance. The data used in this research is secondary data. Sources of data from this study were obtained by downloading the company's 2013-2018 financial statements, which were obtained through a website published by the Indonesian Stock Exchange (IDX) www.idx.co.id. The results of this study indicate that Good Corporate Governance Influences Financial Performance and Leverage does not influence financial performance.